2020
DOI: 10.1177/0003489420909417
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sphenopalatine Ganglion Block on the Postoperative Pain in Patients Undergoing Septorhinoplasty

Abstract: Objectives: This study aimed to evaluate the effect of preoperative sphenopalatine ganglion block (SPBG) on the postoperative pain (POP) in patients undergoing septorhinoplasty (SRP). Methods: A retrospective cohort study was performed. A total of 42 patients that had received septorhinoplasty included in the study. The patients that had received SPBG before the surgery included in the Block group (n:20) and the patients that had not received SPBG before the surgery included in the Control group (n:22). POP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…[ 17 ] The pre-emptive analgesic effect of sphenopalatine ganglion block with different local anaesthetics has been studied in patients undergoing functional endoscopic sinus surgery, which also demonstrated similar findings. [ 19 20 ] The use of nasociliary and infraorbital nerve blocks as the sole anaesthetic technique in outpatient nasal surgeries has shown encouraging results by providing good intraoperative conditions in 20 out of 24 patients. [ 6 ] However, the study reported a failure rate of 13% (4 out of 24 cases).…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] The pre-emptive analgesic effect of sphenopalatine ganglion block with different local anaesthetics has been studied in patients undergoing functional endoscopic sinus surgery, which also demonstrated similar findings. [ 19 20 ] The use of nasociliary and infraorbital nerve blocks as the sole anaesthetic technique in outpatient nasal surgeries has shown encouraging results by providing good intraoperative conditions in 20 out of 24 patients. [ 6 ] However, the study reported a failure rate of 13% (4 out of 24 cases).…”
Section: Discussionmentioning
confidence: 99%
“…В ходе поиска выявили 134 релевантных исследования, 34 из них были дублирующими публикациями. Далее были изучены оставшиеся 100 исследований (2569 пациентов), из них 14 исследований (424 пациента) содержали критерии исключения, то есть КНБ выполнялась как компонент сочетанный анестезии, например применение интраоперационно в лор-хирургии [13] и при хирургии врожденных дефектов верхней челюсти у детей [14], а также те исследования, где КНБ сочеталась с блокадой большого затылочного нерва [15]. Из оставшихся 86 исследований (2145 пациентов) были исключены 13 обзоров и 50 исследований, не являющихся РКИ (1555 пациентов).…”
Section: результаты отбор исследованийunclassified
“…Существуют разные доступы к крылонебному узлу: интраназальный [1], над-и подскуловой [2]. На сегодня крылонебная блокада (КНБ) часто используется как компонент анальгезии в лор-хирургии [3], а также в офтальмохирургии [4]. В данном обзоре сделан акцент на анальгетическом эффекте КНБ как самостоятельного метода обезболивания, вне зависимости от способа выполнения крылонебной блокады.…”
Section: Introductionunclassified
“…The inability to perform an infraorbital blockade to anesthetize during surgery of the inferior orbital rim wall is associated with the displacements of bone fragments in the infraorbital foramen after the fracture [7]. In this regard, the analgesic effect of the pterygopalatine blockade (PPB) is of interest, which is successfully used in otolaryngology, maxillofacial surgery and as an interventional technique for acutemigraine headache, cluster and chronic facial pain, as well as in the treatment of postdural puncture pain syndrome, post-herpetic neuralgia [8,9].…”
Section: Introductionmentioning
confidence: 99%